2021
DOI: 10.1371/journal.pone.0246390
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the plant use knowledge in the middle mountains of Nepal

Abstract: An account of total of 58 plant species including 57 genera and 43 families was reported as useful in ethnomedicine from semi-structured questionnaire survey to the 76 participants of Kaski and Baitadi districts, Nepal. Fieldwork and participatory meetings were carried out between September 2017 and January 2018. A total of 419 emic use reports including 150 from Kaski and 269 from Baitadi were reported from 58 ethnomedicinal plant species. Each species was reported for 2–43 use reports and each participant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…Selection of plants for specific ethnobotanical uses follows two main pathways: (1) random selection, where no regard is taken of the taxonomic affinities, ecological clues, ethnobotanical context or other intrinsic qualities; and (2) targeted or focused selection based on ecological traits (plants in particular habitats with particular growth habits, conservation priorities), or ethnopharmacological appraisals (identifying plants used traditionally to target specific diseases) [ 1 , 2 ]. It is assumed that the selection of medicinal plants in traditional pharmacopeias is non-random and influenced in part by therapeutic efficacy [ 3 ], in part by social and cultural factors [ 4 6 ] and in part by taxonomic affiliation [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection of plants for specific ethnobotanical uses follows two main pathways: (1) random selection, where no regard is taken of the taxonomic affinities, ecological clues, ethnobotanical context or other intrinsic qualities; and (2) targeted or focused selection based on ecological traits (plants in particular habitats with particular growth habits, conservation priorities), or ethnopharmacological appraisals (identifying plants used traditionally to target specific diseases) [ 1 , 2 ]. It is assumed that the selection of medicinal plants in traditional pharmacopeias is non-random and influenced in part by therapeutic efficacy [ 3 ], in part by social and cultural factors [ 4 6 ] and in part by taxonomic affiliation [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite debated [ 8 , 13 ], this method has been frequently used and tested in several geographic contexts, e.g., in Amazonian Ecuador [ 8 , 13 ], in Belize [ 14 ], in Kashmir, India [ 15 ], in Hawai’i, USA [ 11 ], in Pakistan [ 16 ], in Mexico [ 4 ], in South Africa [ 9 , 17 ] and in Italy [ 18 ]. Nonetheless, such hypothesis-driven ethnobotanical studies are scant particularly in plant-rich countries with broad traditional medicinal knowledge like Nepal [ 6 , 19 – 23 ]. Recent studies still focus on medicinal plant diversity, their use patterns and conservation issues [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of such knowledge between individuals in a community is usually differentiated by gender, age or social role. Katul et al [ 61 ] pointed out that in the mid-hills of Nepal knowledge of plant use follows a pattern determined by the available useful plants and sociocultural tradition of the particular area. The significant difference in the case of free listing as well as identification tests between key informants and other informants showed that key informants play a major role as ethnobotanical informants.…”
Section: Discussionmentioning
confidence: 99%
“…Other livelihood strategies include animal husbandry, summer grazing, and collection, use, and trade of forest products. The dominant ethnic groups Gurung and Magar comprised of about 35% of the total population of the area [47], are mountain dwellers, sheep herders, cattle grazers and trans-himalayan traders [34] who often confront with wildlife in the mountain rangelands [33,49,50].…”
Section: Study Area and Site Descriptionmentioning
confidence: 99%
“…The use of forest resources / area for summer grazing, herding, collection of plants and harvesting of forest products i.e. timber, fuel-wood from forests and forest fringes are still persistent among people of studied districts [33,34]. HWCs occurred in human settlement outside PAs while people carrying out such activities [35][36][37].…”
Section: Introductionmentioning
confidence: 99%